1973
DOI: 10.1063/1.1678963
|View full text |Cite
|
Sign up to set email alerts
|

Self-diffusion in liquid ammonia and deuteroammonia

Abstract: Coefficients of self-diffusion have been measured by the spin-echo technique for neat NH] and N0 3 from 200 to 298°K. The data are well represented by D = (4.5±O.2)X 10-] exp [-(2.07±O.02)/RT] for NH3 and by D = (6.0±O.3) X 10-3 exp [-(2.31±O.02)/RT] for N0 3 . The difference in activation energy for self-diffusion between NH] and NO] is shown to be consistent with the viscosity measurements of Hutchison and O'Reilly. These results are interpreted by means of a quasilattice model for self-diffusion in the liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
24
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 16 publications
7
24
0
Order By: Relevance
“…The data agree within experimental error with the SVP data by O'Reilly et al [4]. [5], HF [6], CH4 [7][8][9], CH30H [10], and H2O [11].…”
Section: High Pressure Apparatussupporting
confidence: 79%
“…The data agree within experimental error with the SVP data by O'Reilly et al [4]. [5], HF [6], CH4 [7][8][9], CH30H [10], and H2O [11].…”
Section: High Pressure Apparatussupporting
confidence: 79%
“…The self-diffusion coefficient of saturated liquid ammonia was calculated at temperatures between 203 K and 330 K and compared to predictions by other authors using Experimental data [37,38] (+) and a correlation thereof [39] (−) are shown for comparison. The statistical uncertainty of the present data is within symbol size [40] (open symbols).…”
Section: Self-diffusion Coefficientmentioning
confidence: 99%
“…It is found experimentally that the self-diffusion coefficient (D) of liquid ammonia is strongly temperature dependent [21], and it is not yet possible to model that properly using simulation data [18,22], A self-diffusion coefficient for bulk ammonia calculated in our previous work [18] using the same NH 3 -NH 3 pair potential as in this study, and calculated in [22] are approximately 70% too high and 80% too low, respectively, compared with the experimental value at 277 K [21,23]. However, for the ammonia molecules in the first solvation shell of Ca(II) we obtained D = (3.80± 2.22)x 10^ cm 2 s" 1 and D = (5.75±2.35)xlO -5 cm 2 s" 1 for the simulations with and without three-body corrections, respectively.…”
Section: Dynamical Properties Of the Solutionmentioning
confidence: 99%